Pro PHP Security From Application Security Principles to the Implementation of XSS Defenses - Snyder, Chris; Myer, Thomas; Southwell, Michael (Apress : Imprint: Apress, 2010)
PHP security, just like PHP itself, has advanced. Updated for PHP 5.3, the second edition of this authoritative PHP security book covers foundational PHP security topics like SQL injection, XSS, user authentication, and secure PHP development. Chris Snyder and Tom Myer also delve into recent developments like mobile security, the impact of JavaScript, and the advantages of recent PHP hardening efforts. Pro PHP Security, Second Edition will serve as your complete guide for taking defensive and proactive security measures within your PHP applications. Beginners in secure programming will find a lot of material on secure PHP development, the basics of encryption, secure protocols, as well as how to reconcile the demands of server-side and web application security.